The Relationship Between Economic Status and the Incidence of Stunting in Toddlers Aged 2-5 Years - Henny Vidia Effendy; Surya Mustika Sari (Universitas Islam Lamongan, 2026)
Socioeconomic status affects a family's ability to meet their toddler's nutritional needs. Malnutrition problems, particularly stunting, are closely related to the quality and quantity of food consumed, where the factor determining food quality is income level. The aim of this study is to determine the relationship between economic status and the incidence of stunting in toddlers aged 2-5 years. The research design is correlational analytic with a cross-sectional approach. Economic status is the independent variable and the incidence of stunting is the dependent variable. The population of the study consists of all toddlers experiencing stunting at the Gayaman Village Posyandu, totaling 19 toddlers. The sample was taken using a total sampling technique comprising 19 respondents. Data were collected using socioeconomic questionnaires and observations of children's height and age. The data collected were tested using the Spearman rho test. The results of the study indicate that almost all respondents with high economic status toddlers are in. The results of the Pearson correlation test showed a value of ρ = 0.010 < α = 0.05, thus H1 is accepted, meaning there is a relationship between economic status and the incidence of stunting. It is expected that health cadres monitor the height of toddlers so that early screening can be conducted for those at risk of stunting. In addition, cadres must also provide guidance to toddlers who are experiencing stunting and coordinate with health centre staff for their management.